(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
INTRODUCTION Pain has been defined as an unpleasant sensory and emotional experience associated with actual or potential tissue damage or described in terms of such damage.1 Pain is the most dreaded problem which a person fears after any surgery. The transversus abdominis plane (TAP) block is an anaesthesia technique that provides analgesia to the parietal peritoneum as well as the skin and muscles of the anterior abdominal wall.4 Since the thoracolumbar nerves originating from the T6 to L1 spinal roots run into this plane and supply sensory nerves to the anterolateral abdominal wall5, the local anaesthetic spread in this plane can block the neural afferents and provide analgesia to the anterolateral abdominal wall. AIM AND OBJECTIVES Aim of study was to compare 0.25% Ropivacaine and 0.25% Bupivacaine in TAP block for postoperative analgesia in patients undergoing Abdominal Surgeries. The following parameters were compared: A. To study the effectiveness of transverses abdominis plane block for post-operative analgesia in Abdominal Surgeries. B. To compare the duration of analgesia and its effectiveness conferred by 0.25% Ropivacaine and 0.25% Bupivacaine. C. Total requirement of rescue analgesia. D. To watch for occurrence of side effects, if any MATERIALS AND METHODS A comparative clinical study was carried out on 60 adult patients belonging to ASA grade I or II, scheduled for elective Abdominal Surgeries. All patients were administered spinal anaesthesia with bupivacaine heavy 0.5%, 2.0-4.0 ml with 25 G spinal needle at L2-L3 or L3-L4 vertebral interspace. The patients were randomly allocated in two groups and study drug was injected at the end of surgery according to the group. The volume of administered drug kept constant (20 ml). Group I: Patients received TAP BLOCK on each side with 10ml 0.25% Ropivacaine. Group II: Patients received TAP BLOCK on each side with 10ml 0.25% Bupivacaine. CONCLUSION Transversus Abdominis Plane Block (TAP Block) provides better postoperative analgesia in various abdominal surgeries. 0.25% ropivacaine and 0.25% bupivacaine are equally effective in TAP block and provides effective postoperative analgesia but ropivacaine group shown longer duration of action compared to bupivacaine which was statistically significant without causing any increased adverse effects.